LITERATURE AND HUMAN VALUES: AN EXPERIENCE FROM AN EFL CLASSROOM AT PSU, PATTANI - Suraiya Sulaiman (Universitas Ahmad Dahlan)
Being a rich source of language and culture, literature has been an ideal tool for the study of a language. As literature offers a bountiful and extremely varied body of written material that deals with enduring human issues, it facilitates in enhancing students’ language proficiency as well as expanding their knowledge horizon. Accordingly, literature seems to provide answers for the question posed by the 4th UAD TEFL International Conference: how to teach English in order to boost students’ language proficiency while empowering them with knowledge, skills and attitude in endorsing sustainable development and promoting global awareness. In this article I will share my experience from my literature class at PSU, where I deal with the concerned question. I use two main literary works, A Street Cat Named Bob (2012), a biography by James Bowen and The Kite Runner (2003), a novel by Khaled Hosseini, to teach my students about human values such as love, loyalty, courage and social justice. At the same time, I introduce them to the world’s current issues such as diaspora, immigration, war and the idea of multicultural society.